Media Sosial Sebagai Sarana Pembinaan Bahasa Indonesia di Era Revolusi Industri 4,0 (Di Era Digital) - Nur Hasanah; Edi Syaputra (Universitas Dehasen Bengkulu, 2022)
Social media is a medium/means used for long-distance communication needs, and a means to obtain information through application devices with an internet network. Through the internet network, people can communicate quickly to establish relationships with other people, conduct entrepreneurship online, provide and get information quickly without knowing the place and time. Indonesian language subjects are compulsory subjects taught at the elementary, secondary and even higher education levels. The basic competencies that must be mastered by students in Indonesian language lessons are the same as lessons in several literary languages, one of which is Balinese language which includes aspects of language skills, namely listening, speaking, reading, and writing. Reading and writing are included in literacy skills. The development of the world at this time has entered the era of the industrial revolution 4.0, the form of human life has been based on information. Therefore, digital literacy needs to be developed in the world of education to be more prepared to face the era of education in the 21st century. This type of research is a qualitative research with a descriptive method. Improving self-ability in the use of Indonesian, as well as increasing positive attitudes so that people have awareness, pride, and loyalty to Indonesian language norms in the digital era.